Onconephrology: What Should the Internist Know About Targeted Therapy in Solid Tumors? (Iranian Journal of Kidney Diseases, 2016)
Advances in medical oncology has led cancer patients to live longer. Moreover, the field of molecular oncology is rapidly evolving, new therapies emerge, and drugs are approved quickly. This has led nephrologists to encounter new and partially unrecognized treatments of the targeted therapy agents with kidney adverse effects. These agents fall mainly into 2 categories affecting the vascular endothelial growth factor and endothelial growth factor pathways. This review covers the incidence of kidney disease induced by these agents, pathophysiologic mechanisms, and clinical presentation, and is the first to recommend an adequate management for each pathophysiology.